2008
DOI: 10.1167/8.15.16
|View full text |Cite
|
Sign up to set email alerts
|

Competition between color and luminance for target selection in smooth pursuit and saccadic eye movements

Abstract: Visual processing of color and luminance for smooth pursuit and saccadic eye movements was investigated using a target selection paradigm. In two experiments, stimuli were varied along the dimensions color and luminance, and selection of the more salient target was compared in pursuit and saccades. Initial pursuit was biased in the direction of the luminance component whereas saccades showed a relative preference for color. An early pursuit response toward luminance was often reversed to color by a later sacca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
2
4
0
Order By: Relevance
“…The fact that spontaneous saccade directions are aligned with the surface depth gradient of a purely disparity-defined plane as shown by Wexler and Ouarti (2008) excludes the possibility that the luminance gradient, always correlated with the perspective tilt axis, guided saccade directions in that and the current study. Earlier, Vishwanath and Kowler (2004) reported that saccade landing positions were related to the 3D geometric cues of the saccade targets revealing that depth cues are important in driving saccades, whereas luminance has been shown to have at the most a moderate effect on saccade landing positions (Melcher & Kowler, 1999;Spering, Montagnini, & Gegenfurtner, 2008). Here we have shown that when two depth cues are present, the axis of spontaneous saccades combines the tilts of the two cues in the same way, and with the same weights, as perception does.…”
Section: Discussionsupporting
confidence: 61%
“…The fact that spontaneous saccade directions are aligned with the surface depth gradient of a purely disparity-defined plane as shown by Wexler and Ouarti (2008) excludes the possibility that the luminance gradient, always correlated with the perspective tilt axis, guided saccade directions in that and the current study. Earlier, Vishwanath and Kowler (2004) reported that saccade landing positions were related to the 3D geometric cues of the saccade targets revealing that depth cues are important in driving saccades, whereas luminance has been shown to have at the most a moderate effect on saccade landing positions (Melcher & Kowler, 1999;Spering, Montagnini, & Gegenfurtner, 2008). Here we have shown that when two depth cues are present, the axis of spontaneous saccades combines the tilts of the two cues in the same way, and with the same weights, as perception does.…”
Section: Discussionsupporting
confidence: 61%
“…According to our results, variations in saccadic measures may reflect reading proficiency and general cognitive functioning, and not only the effect of age as reported in developmental studies ( Munoz et al, 1998 ; Klein et al, 2003 ; Pratt et al, 2006 ), task manipulations ( Spering et al, 2008 ), or neurological dysfunction, as reported previously for clinical populations ( LeVasseur et al, 2001 ; Munoz et al, 2003 ; Machado and Rafal, 2004 ; Karatekin, 2006 ; Rivaud-Pechoux et al, 2007 ; Levy et al, 2008 ). Taking educational and cognitive factors into account in studies of this kind will shed light on the application and interpretation of eye-movement assessment in the fields of basic or clinical research.…”
Section: Discussionsupporting
confidence: 84%
“…Three target contrast conditions ( Figure 1) were chosen to manipulate the processing of visual signals, as described in the Introduction (Thompson, 1982;Doma & Hallett, 1988;Stone & Thompson, 1992;Hawken & Gegenfurtner, 2001;Ludwig et al, 2004;Spering et al, 2005;Braun et al, 2008;Spering et al, 2008). For the high luminance contrast condition the peak luminance contrast of the white Gaussian target blob was set to 0.8.…”
Section: Targets Contrastsmentioning
confidence: 99%
“…We used three different contrast manipulations to selectively attenuate processing mechanisms for position and velocity. It is well established that under some conditions color isoluminance attenuates motion and speed perception (Cavanagh, Tyler, & Favreau, 1984;Lu, Lesmes, & Sperling, 1999; for reviews, see Gegenfurtner & Hawken, 1996;Cropper & Wuerger, 2005) and smooth pursuit eye movements (Braun et al, 2008;Spering, Montagnini, & Gegenfurtner, 2008). However, it does not affect positional accuracy (Krauskopf & Farell, 1991), or the accuracy of saccades to static chromatic targets (White, Kerzel, & Gegenfurtner, 2006).…”
Section: Introductionmentioning
confidence: 99%